Analisis Landasan Ilmu Pengetahuan dan Teknologi dalam Pengembangan Kurikulum - Farrah Camelia (SAP (Susunan Artikel Pendidikan), 2020)
The progress of a country is supported by the quality of human resources in it. technological progress and knowledge are two things that are very influential on the development of the country. Future challenges include the development of information technology, the convergence of science and technology, the advancement of creative and cultural industries, the influence and impact of science, demanding the implementation of curriculum development with a more comprehensive foundation of science and technology. This study aims to broaden the reader's insight on the importance of improving the quality of human resources by improving education in Indonesia, one of which is through the development of a curriculum based on science and technology. The research methods used was the qualitatif descriptive approach. The results of the study explained that, educational institutions especially the school path must be able to support and anticipating the progress of science and technology. Teaching materials or materials should be the result of the development of contemporary science and technology, both related to the results of information acquisition, or how to obtain this information and use it for the community. It takes the use, development and mastery of science and technology in order to have implications for the development of human resources.